2020
DOI: 10.1007/s10741-020-10036-y
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin C: historical perspectives and heart failure

Abstract: Vitamin C (Vit C) is an ideal antioxidant as it is easily available, water soluble, very potent, least toxic, regenerates other antioxidants particularly Vit E, and acts as a cofactor for different enzymes. It has received much attention due to its ability in limiting reactive oxygen species, oxidative stress, and nitrosative stress, as well as it helps to maintain some of the normal metabolic functions of the cell. However, over 140 clinical trials using Vit C in different pathological conditions such as myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 142 publications
(220 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, a meta-analysis of RCTs showed that vitamin C supplementation has no effects on major cardiovascular outcomes such as CVD mortality and myocardial infarction (Al-Khudairy et al, 2017). There is still a need to identify the role of vitamin C in mitigating cancer treatment-induced heart failure (Malik et al, 2020) and other risks of CVD, including cardiomyopathies, arrhythmias and myocarditis/pericarditis in long-term cancer survivors (Berretta et al, 2020). However, the evidence is limited because many trials of vitamin C (and E) supplementation did not report protective effects on risks of CVD, such as blood pressure, arterial stiffness, endothelial function, or left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis of RCTs showed that vitamin C supplementation has no effects on major cardiovascular outcomes such as CVD mortality and myocardial infarction (Al-Khudairy et al, 2017). There is still a need to identify the role of vitamin C in mitigating cancer treatment-induced heart failure (Malik et al, 2020) and other risks of CVD, including cardiomyopathies, arrhythmias and myocarditis/pericarditis in long-term cancer survivors (Berretta et al, 2020). However, the evidence is limited because many trials of vitamin C (and E) supplementation did not report protective effects on risks of CVD, such as blood pressure, arterial stiffness, endothelial function, or left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Specific transporting systems are involved in the absorption of vitamin C as well as its intracellular distribution (reviewed in [8,10]). Historically, vitamin C transport across cell membranes had been an area of extensive research in neurobiology.…”
Section: Intracellular Dynamics Of Vitamin Cmentioning
confidence: 99%
“…This high concentration is due to selective intracellular accumulation via a vitamin C transport system present in the plasma membrane [9] (see section 'Intracellular dynamics of vitamin C' for more details). The high intracellular concentration of vitamin C in mammalian tissues is in line with its essential roles in maintaining physiological homeostasis (reviewed in [4,5,10]). In this Mini-Review, we first describe the novel redox properties and functions of vitamin C, and then discuss major recent research evidence supporting its multitasking functions in controlling oxidative stress and inflammatory responses and in treating sepsis, a major contributor to the global burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C is a water-soluble micronutrient ,that is, abundant in natural rich sources such as fresh fruits and green leafy vegetables (Devaki and Raveendran, 2017). Vitamin C is a powerful reducing agent and a broad-spectrum antioxidant that fights a wide range of free radicals, including ROS (Malik et al, 2021). Vitamin C is involved in the first line of antioxidant defense acting as an excellent donor of electrons for free radicals that need electrons to regain their stability (Zhitkovich, 2021).…”
Section: Vitamin C (Ascorbic Acid)mentioning
confidence: 99%